Energy and Finite Element Methods in Structural Mechanics: SI Units Edition - Shames (Irving H); Dym (Clive L) (1995)
Energy ; Finite Element Methods ; Structural Mechanics
Keywords: Energy ; Finite Element Methods ; Structural Mechanics